Understanding the Theory of Consumption in the Context of a Developing Economy - Oke, David Mautin; Bokana, Koye Gerry (Journal of Economics and Behavioral Studies, 2017)
This paper synthesizes the theory of consumption using some Nigerian contexts. The argument on what determines consumption is yet an unfinished task. We tested the general consumption function using Nigerian data covering 1981-2012. Based on the diagnostics, we employed a vector autoregression-in-first difference approach. The result shows that previous incomes (up to two lags) may not be significant in influencing consumption in Nigeria but previous consumption levels (up to two lags) attained may do. In addition, consumers in Nigeria may reduce their consumption in the current year based on their knowledge of previous year consumption but may raise the current consumption level due to their experience of last two years consumption. This corroborates suggestions that macro-econometricians must analyze consumption beyond the general consumption function. The pattern of historical data also suggests that consumption may be difficult to predict in Nigeria. Therefore, government of Nigeria may succeed in influencing its aggregate demand which consumption is the major component if its income and tax policies are permanent, rather than being temporary.